THE PUBLIC PARTICIPATION IN COMMUNITY DEVELOPMENT OF THE NAKHOK SUB - DISTRICT ADMINISTRATIVE ORGANIZATION, MUANG SAMUTSAKHON - Dockjan, sasiprapa; Sartngern, Pachara (Journal of MCU Phetchaburi Review, 2025)
This research is mixed-method research. The objective is to study the public participation level, the differences between personal characteristics and public participation, and the causal relationship between factors influencing public participation. The sample group consisted of 365 people living in Na Khok Subdistrict, Mueang Samut Sakhon District and 8 key informants. The research instruments were questionnaires and interviews. Data was analyzed using a computer program. The statistics used in the research were percentage, mean, standard deviation, one-way variance, multiple regression analysis, and content analysis techniques. The research results found that the public participation level in community development of Na Khok Subdistrict Administrative Organization was at a moderate level. And the public participation factor has a statistically significant causal relationship with public participation in community development.